A Contextual Approach-Based Teaching Module to Facilitate Students' Mathematical Communication Skills on the Topic of Straight Line Equations - Sri Yuliani; Maimunah Maimunah; Kartini Kartini (Juring (Journal for Research in Mathematics Learning), 2025)
Mathematical communication skills are essential for students because they help convey their mathematical ideas through language, notation, symbols, or images. This study aims to develop a teaching module based on a valid, practical contextual approach to facilitate the development of mathematical communication skills among phase-D students. The research conducted was Research and Development (R&D) using a 4D model consisting of the define, design, develop, and disseminate stages. The development research instruments consisted of a validation sheet and a practicality questionnaire. The validation results stated that the teaching module was classified as very valid. Meanwhile, the results of the practicality test among 30 students were very practical. Thus, the teaching module, designed with a contextual approach, met the validity and practicality criteria and can be applied in the teaching and learning process to support students in understanding mathematical concepts through relevant examples from everyday life and in communicating mathematical ideas meaningfully